Activation of Durian Skin Biomass with H2SO4 Activator on the Absorption of Lead from its Solution - Said, Irwan; Riski, Fahrul; Afadil, Afadil; Ningsih, Purnama (Universitas Tadulako, 2023)
Research has been carried out on the bioabsorption of lead (Pb) using durian skin biomass (Durio zibethinus) which has been activated using an H2SO4 activator. The durian skin sample used was durian skin from Central Sulawesi. The processing technique to remove lead (Pb) from liquid waste was carried out by an adsorption process. The adsorption process is an effective purification and separation technique used in industry because it is more economical and simple in treating wastewater and is a technique that is often used to reduce metal ions in wastewater. This study aims to determine the mass and contact time of the adsorption of Pb by durian skin biomass. Determination of the adsorbed metal used atomic absorption spectrophotometry (AAS). The results obtained showed that the optimal Pb ion adsorption occurred at a weight of 2.5 grams with an absorption capacity of 99.94 %. While the optimal Pb ion adsorption occurred at a contact time of 40 minutes with an absorption capacity of 99.94 %.